Pengembangan Media Pembelajaran Matematika Berbantuan Google Sites pada Materi Sistem Persamaan Linear Dua Variabel - Arnisya, Melinda Fahriani; Luritawaty, Irena Puji; Sumartini, Tina Sri (Faculty of Teacher Training and Education, 2024)
It is important to continue developing digital mathematics learning media. This research was conducted to develop learning media assisted by Google Sites on the material Systems of Linear Equations in Two Variables and to analyze the feasibility of this learning media. This research is descriptive research with the research and development method of the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. The subjects for this learning media trial were 39 students in class VIII of one of the private junior high schools in Garut Regency. Based on the research results, this media meets the criteria for validity and practicality as a learning media product. This is known from: (1) the validity of learning media, which is based on the results of an assessment of the validity of the media and material, showing valid results with revision, with a material achievement percentage of 92.7% and a media achievement percentage of 83.3%; (2) the practicality of learning media, as assessed from the student response questionnaire, obtained a percentage of 74.25%, indicating results that fall into the practical category.